Steinbeck's Father and Family - unknown:::Creator::::::::::::
From left to right: Herbert Eldredge Steinbeck (age 5), John Ernst Steinbeck (JES) (age 2), Charles Minor Steinbeck (age 7). Sons of Johann Adolph Steinbeck (1832-1913) and Almira Ann Dickson Steinbeck (1828-1923). John Ernst Steinbeck was John Steinbeck's father. Charles's middle name probably derives from Clorinda Minor, who was a US-born missionary leader near Jaffa, and who died in 1855. Digital copy only. No hard copy.